2017
DOI: 10.1111/joor.12578
|View full text |Cite
|
Sign up to set email alerts
|

A 5‐year longitudinal study of association of maximum bite force with development of frailty in community‐dwelling older adults

Abstract: SummaryTo determine whether maximum bite force (MBF), an objective measure of oral function, is associated with development of frailty in community-dwelling older adults. This prospective cohort study included community-dwelling Japanese adults aged 75 years at baseline (n = 322). Baseline MBF was measured using an electronic recording device (Occlusal Force-Meter GM10). Follow-up examinations, including physical fitness and anthropometric evaluation and structured questionnaires, were administered annually ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
74
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(90 citation statements)
references
References 28 publications
2
74
1
Order By: Relevance
“…The characteristics of the included studies are presented in Table . Five studies provided data from a combined population of 3086 subjects in 3 countries Mexico, Japan, and UK . The number of participants ranged from 322 to 1151.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The characteristics of the included studies are presented in Table . Five studies provided data from a combined population of 3086 subjects in 3 countries Mexico, Japan, and UK . The number of participants ranged from 322 to 1151.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, all the studies indicated the exclusion of individuals with frailty at baseline of the study from the analysis. Four studies accounted for age, sex, chronic diseases (mostly diabetes) and socio‐economic status, except for one study that accounted for all these factors but not socio‐economic status . In terms of the outcome, all the studies had long follow‐up periods (2‐5 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…16 The study also reported that the need for dental prostheses was associated with a higher likelihood of frailty (OR 1.84, 95% CI 1.13-3.00). 21,22 These studies provide further evidence that oral and dental health might be closely related to frailty, as well as to the risk factors for frailty. Thus, the study suggests that there might be an association between oral health problems and frailty, but that this is not conclusive.…”
Section: Explanationmentioning
confidence: 70%